PENGARUH PROMOSI DAN KUALITAS PELAYANAN KARTU KREDIT TERHADAP LOYALITAS NASABAH PADA PT BANK NEGARA INDONESIA KANTOR CABANG MATRAMAN JAKARTA TIMUR - Tira Sri Yulistiani; Rani Rani; Purwatiningsih Purwatiningsih (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2023)
The growing number of credit card users in Indonesia is considered to have a fairly high poltelnsial market. This study uses associative research quantitative approach which is analyzed using multiple linear regression analysis with SPSS version 26.0 software. The population in this research is Bank BNI customers. The sample was determined based on the random sampling technique method. The data collection technique used a questionnaire distribution of 106 people from the number of Bank BNI East Jakarta customers. Hypothesis testing using the T-test and F-test. The research conclusion concluded that the promotion and quality of credit card services had a significant positive effect on customer loyalty of PT Bank Negara Indonesia Matraman Branch Office, East Jakarta.